Water Supply Scheme in Morotai Island - Wulan Seizarwati; Heni Rengganis; Muhshonati Syahidah; Waluyo Hatmoko; Derry Prasetya (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
Morotai Island is designated as one of the National Tourism Strategic Area, and has increased demand for pure water. It is known as a dry area where water is difficult to obtain, and therefore, it is necessary to prepare a supply scheme to meet the island's demand. Hence, this study aims to obtain supply protocol from various available sources, in order to meet all water demands, especially for tourism sector development. The several methods used in this research include demand calculation for domestic, industry, irrigation, livestock, and tourism; rainfall-runoff simulation using Wflow model and estimation of groundwater availability using the baseflow recession method. Furthermore, surface balance shows the water availability in each sub-districts is not able to meet the demands. To overcome this problem, a supply scheme has been prepared, e.g. surface water utilization by constructing free intake in North Morotai, groundwater use by constructing dug and drilled wells in many locations, especially coastal areas, spring water utilization by creating a collection system (broncaptering) in Jaya, East and South Morotai. Furthermore, small islands can utilize springs and shallow dug wells, to prevent seawater intrusion from affecting the quality. The scheme suggests an appropriate infrastructural support to supply local communities, as well as develop the Island to be the new primary tourism center in Indonesia.